Pengaruh Perbedaan Media Rendaman terhadap Karakteristik Sensoris dan Fisikokimia Nori Rumput Laut Ulva Lactuca dan Eucheuma Cottonii - Jason P Kenardi; Marito G. Sitanggang; Luh Dian Rna Fajarini; Ni Luh Ari Yusasrini (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
This study aimed to evaluate the effects of different soaking media mineral water, rice-wash water, 1% Ca(OH)₂, and 1% citric acid on the sensory, chemical, and physical qualities of nori produced from a mixture of Ulva lactuca (95%) and Eucheuma cottonii (5%). The results showed that the soaking treatments had a significant effect on the color, aroma, flexibility, crispness, moisture content, and hardness of the nori. The mineral-water treatment produced the best overall performance, with the lowest moisture content (3.01%), the highest flexibility score (3.03), and the highest panelist acceptance score (3.58). The 1% Ca(OH)₂ treatment provided the best green-color stability (a* –7.00) and the lowest hardness (9.847 N), whereas the 1% citric acid treatment resulted in the most degraded coloration (a* 2.70) and the highest hardness (21.076 N). Differences among treatments were influenced by pH-driven modifications of polysaccharide structures, ionic interactions, and depolymerization mechanisms. Overall, rice-wash water was identified as the most effective soaking medium for improving the quality of locally produced nori made from U. lactuca and E. cottonii.